STRENGTHENING BRAND IMAGE OF PESANTREN BASED ON TWO-WAY SYMEIRICAL MODEL THROUGH GENERATION Z - Munir, Zainal; Izzatul Munawwaroh; Mudarris, Badrul (Managere: Indonesian Journal of Educational Management, 2024)
This research explores how to strengthen a brand image based on the two-way symbolic model through Generation Z. This research uses a qualitative case study approach. The research subjects included caregivers, Pesantren heads, administrators, guardians, alums, the community, and students. Data collection techniques include observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion. The research results show that applying a two-way symmetrical communication model can strengthen the brand image of Pesantren through interaction with Generation Z, which can be proven by several indicators, namely dialogism, involvement of Generation Z, messaging adaptation, and relationships. A two-way symmetrical communication model can increase involvement and interaction between administrators, students, and the community. Generation Z has a crucial role in strengthening the image of Pesantren through social media campaigns. Open communication and responsive adaptation of messages to feedback help build a positive image of Pesantren. The active involvement of students in social and religious activities strengthens relationships with the community, making Pesantren an inclusive and responsive institution that contributes significantly to the welfare of the local community.